Residents’ perceptions of urban nature and nature-based solutions in Ouagadougou - Combary, Youmanli Enok Ferdinand; Atchrimi, Bernard Tossou (Frontiers in Sustainable Cities, 2024)
With rapid urban growth posing major environmental and social challenges, nature-based solutions (NbS) are at the heart of urban strategies for sustainability and resilience. They help to maintain biodiversity and respond to contemporary climatic and societal challenges. To be best planned and implemented, they need to consider geographical and socio-cultural contexts, including the local perceptions and experiences of residents. Lack of information on social aspects and absence of data are often obstacles to implementation. This article is part of a study on the challenges and opportunities of implementing nature-based solutions for sustainable urban development in Ouagadougou. This study aimed to explore how socio-demographic factors influence perceptions and experiences of urban nature, and to identify implications for urban planning and the implementation of nature-based solutions. Questionnaire surveys were conducted among 401 people, with different socio-demographic profiles and different places of residence. Group interviews with 20 people were then conducted to triangulate the collected data to understand the different interactions between the residents and urban nature. The main results show that, overall, residents perceive urban nature positively. Perceptions and experiences of nature vary considerably according to respondents' socio-demographic profiles and proximity to green spaces. The study also identified the need for appropriate maintenance and management, as well as participatory planning to align nature-based solutions with residents' expectations, with a focus on benefits. The recommendations offered to practitioners, planners, and those involved in urban development for implementing nature-based solutions and identifying limitations, such as a lack of revenue data, provide a solid basis for future action.